Spatial Distribution of Key Sectors of West Kalimantan, Indonesia - Harahap, Rina Muthia; Koestoer, Raldi Hendro (Universitas Muhammdaiyah Surakarta, 2014)
ASEAN Economic Community will be implemented in 2015, while West Kalimantanprovince which is located in 2 Sub-Regional Cooperations of ASEAN , yet to be widely discussed by regional economic experts in terms of itsregional potentials. Multi-sector expressions often generalized in majorcategories, seem to be uncleared to share what key sectorsindicated and where they distribute in the region concerned.. Based on this,the paper proposes a combination approach of multi-sector model and inter-linked in spatial dimensions. Input-output method and Location Quotient models introduced and applied in the case of West Kalimantan province in the efficiency of its development efforts towards a Green Plan.